Coronavirus Disease 2019 (COVID-19) Associated Hemolytic Uremic Syndrome in a Toddler - Kristie Searcy; Apoorva Jagadish; Patricia Pichilingue-Reto; Radhakrishna Baliga (Case Reports in Pediatrics)
Coronavirus disease 2019 (COVID-19) is a heterogenous, predominantly pulmonary disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that has resulted in catastrophic illness around the world. Thrombotic microangiopathy (TMA) is a triad of hemolytic anemia, thrombocytopenia, and end organ damage. This is present in severe cases of COVID-19 and in hemolytic uremic syndrome (HUS) commonly caused by Escherichia coli (E.coli) 0157:H7. We report a novel case of a toddler who presented with classic features suggestive of HUS characterized by bloody diarrhea followed by thrombocytopenia, hemolytic anemia, and acute kidney injury, in whom a polymerase chain reaction (PCR) test for SARS-CoV-2 was positive.